1994
DOI: 10.1063/1.357859
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-vacuum scanning electron microscopy characterization of the growth of Fe on CaF2/Si(111): Selective nucleation on electron-beam modified surfaces

Abstract: The initial stages of Fe island growth on electron-beam modified and unmodified CaF2/Si(111) surfaces were studied with a nanometer lateral spatial resolution ultrahigh-vacuum scanning electron microscope. Fe coverages between 7 and 8 ML (deposition rates from 0.12 to 0.19 ML/min, 1 ML=7.7×1014 atom/cm2) grown on room temperature through 300 °C CaF2/Si(111) relaxed and unrelaxed substrates produced a relatively uniform distribution of islands that cover 23% of the substrate with an island density of 7.4×1012 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The growth behavior of Ca on CaF 2 ͑111͒ has not yet been reported in the literature, however, similar elongated island structures have been observed for the growth of Fe on CaF 2 ͑111͒ [18,19]. The lattice constant of calcium is ϳ2% larger than that of CaF 2 .…”
supporting
confidence: 56%
“…The growth behavior of Ca on CaF 2 ͑111͒ has not yet been reported in the literature, however, similar elongated island structures have been observed for the growth of Fe on CaF 2 ͑111͒ [18,19]. The lattice constant of calcium is ϳ2% larger than that of CaF 2 .…”
supporting
confidence: 56%
“…A straightening of the substrate steps and the formation of regular stripe patterns was observed [99]. A similar expression of the film-substrate symmetry in strain relief structures was found by Heim et al, who observed saw-tooth pattern upon annealing of stepped structures of CaF 2 grown on Si (111) [91].…”
Section: Film Structures Resulting From Strain Reliefsupporting
confidence: 76%
“…The formation of Co islands on the CaF 2 surface (instead of 2D growth) is basically determined by the much higher surface free energy of the metal with respect to CaF 2 [13,14]. Co wets the buffer layer insufficiently to provide coalescence of the islands.…”
Section: Resultsmentioning
confidence: 98%